Can we use thermal imaging to evaluate the effects of carpal tunnel syndrome surgical decompression?. Issue 39 (September 2017) - Baic, Agnieszka; Kasprzyk, Teresa; Rżany, Michał; Stanek, Agata; Sieroń, Karolina; Suszyński, Krzysztof; Marcol, Wiesław; Cholewka, Armand
Abstract : Abstract: Research is intended to verify if thermal imaging can be used in diagnosing and monitoring the carpal tunnel syndrome (CTS). This disease is not easy to diagnose using traditional methods. Also, the difficulties in monitoring carpal tunnel surgery effects necessitate new, noninvasive method, which gives more information. The research group consists of 15 patients with CTS and control group of healthy people. All patients who were examined before surgery were also tested 4 weeks after surgery, to check the effects of treatment. In addition a lot of our patients had or will have open carpel tunnel release surgery. Diagnosis of CTS was performed by thermal imaging in both hands from phalanges to the area of the wrist on the external and palmar side of the palm. Using infrared (IR) camera one can observe high temperature gradient on hand-tested areas and these differences prove the diagnosis. Moreover patients after surgery have better temperature distribution and it was closer to control group. Results prove that surgery is the best, and currently, the only method to treat CTS. Thermal imaging may be helpful in diagnosing CTS.